The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1590/1519-6984.270354
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dormancy break and germination of safflower seeds: the role of GA3, light and cold temperatures

B. N. P. Silva,
T. E. Masetto,
J. V. S. Zanzi
et al.

Abstract: The safflower crop is considered a great alternative for crop rotation since drought tolerance and low production cost are attractive for its choice. However, safflower seeds show dormancy soon after dispersal from the mother plant, making it difficult to successfully establish plants using newly harvested seeds. The influence of temperature, gibberellin and light/dark on dormancy break of safflower seeds during storage were investigated. In a completely randomized design, freshly harvested seeds or stored for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Dormancy of safflower seeds is pronounced soon after removal from the parent plant. It was indicated that recently harvested seeds could efficiently germinate at 10 °C in the dark, while seeds dry-stored at 20 °C had low germination percentages (Silva et al, 2023). As for fertilizers, the application of plant growth promoting rhizobacteria (Azospirillum and Azotobacter) not only The biological characteristics and application of safflower.…”
Section: Agronomic Conditions Of Safflower Cultivationmentioning
confidence: 99%
“…Dormancy of safflower seeds is pronounced soon after removal from the parent plant. It was indicated that recently harvested seeds could efficiently germinate at 10 °C in the dark, while seeds dry-stored at 20 °C had low germination percentages (Silva et al, 2023). As for fertilizers, the application of plant growth promoting rhizobacteria (Azospirillum and Azotobacter) not only The biological characteristics and application of safflower.…”
Section: Agronomic Conditions Of Safflower Cultivationmentioning
confidence: 99%